PC-Based ATM Network Simulator / Lai Weei Shan - Lai, Weei Shan (2000)
Asynchronous Transfer Mode (ATM) has emerged as a very high-speed transmission technology. The barrage of technological advancements has continuously enhanced the network performance. There is an increasing dependence on the network. Thus, there is a need to accurately predict the impact of network and applications changes in the dynamic network environment.The project is divided into two parts: Part one: Study the concept of ATM and the important issues regarding it. Various existing simulators and applications on A TM are studied to plan for an up to date simulator. Part two: Develop a PC Based simulator. This is motivated by the importance of an ATM network simulator and the changing environment in computer world. The simulator is developed to provide a simulated network management environment of unlimited scale at a fraction of cost, compared to the expense of testing it out in a real network environment. With this simulator, further research on ATM can be carried out smoothly.